Nonsurgical Management of Adductor-related groin pain with Ultrasound-Guided Platelet-Rich Plasma Injection and Physical Therapy in a Competitive Soccer Player: A Case Report - Giorgio Zeppieri; Micheal S Smith; Ryan P. Roach (North American Sports Medicine Institute, 2024)
# Introduction Adductor-related groin pain involves an injury to the common aponeurosis connecting the rectus abdominus and adductor longus to the pubis. It commonly occurs in sports that require cutting and pivoting and can result in significant loss of playing time. Platelet-Rich Plasma (PRP) is often indicated for treatment of musculoskeletal disorders and may represent an alternative treatment for patients with adductor-related groin pain. The purpose of this case report is to describe the non-surgical management of adductor-related groin pain in a competitive soccer player with a with an ultrasound (US)-guided PRP injection and physical therapy management. # Case Description A 17-year-old male competitive soccer player with right-sided adductor-related groin pain was treated with an US-guided PRP and a multi-phased physical therapy regimen based on tissue healing and individual patient/criteria progression. The patient completed 12 physical therapy sessions over six weeks post PRP injection. # Outcomes At the end of treatment, clinically meaningful improvements were observed in pain intensity, passive range of motion, strength (handheld dynamometry, Biodex), functional tests, psychosocial (OSPRO-YF) and patient-reported outcomes (HAGOS, LEFS). The subject returned to sport at six weeks post injection without limitation and at three months follow up, the subject reported that he had returned to 95% of his previous level of play. # Discussion This case report may offer support for PRP as an alternative treatment in the management of adductor-related groin pain. Incorporation of PRP as an adjunct to physical therapy led to improvements on all outcomes that surpassed the clinical significance change criteria. # Level of evidence 5